A case report of Hypocomplementemic urticarial vasculitic syndrome presenting with Renal failure - Hopkins, Amy M; Gibbs, Angela M; Griffiths, Ryan S; Avasare, Rupali S; Khoury, Firas G (Journal of Clinical Nephrology, 2018)
We present a case of hypocomplementemic urticarial vasculitic syndrome (HUVS) who developed severe renal failure requiring ICU-level care. Our patient is a 66-year-old man who presented with abdominal pain, rash, confusion, oliguria, and shortness of breath. He was found to be in acute renal failure with leukocytosis and elevated lactate. Work-up for infectious, autoimmune, and hematologic malignant diseases was negative. The presence of chronic urticaria, abdominal pain, hypocomplementemia, and leukocytoclastic vasculitis on skin biopsy confirmed the diagnosis of HUVS. He required hemodialysis for renal failure as well as gastrostomy tube placement for nutritional support secondary to the development of mucosal ulcers, a rare finding in HUVS. He recovered with several months of high-dose steroids and hemodialysis. This case highlights the effectiveness of steroids for initial treatment of HUVS, and the relapsing and remitting nature of the disease. Providers should also be aware of the broad range of presenting symptoms such as mucosal lesions that may require nutritional support. Interestingly, unlike many previously reported cases of HUVS, our patient had not yet developed signs and symptoms of systemic lupus erythematosus, which often overlaps with HUVS.